Physiological response of Clostridium ljungdahlii DSM 13528 of ethanol production under different fermentation conditions. (February 2015) - Xie, Bin-Tao; Liu, Zi-Yong; Tian, Lei; Li, Fu-Li; Chen, Xiao-Hua
Highlights: A unique alternative acetate re-assimilation pathway triggered ethanol production. Putative aldehyde oxidoreductase aor1 involved in this alternative pathway. Accumulation of external acids induced the shift to solventogenesis. A trace amount of CaCO3 increased ethanol and acetate production. Abstract: In this study, cell growth, gene expression and ethanol production were monitored under different fermentation conditions. Like its heterotrophical ABE-producing relatives, a switch from acidogenesis to solventogenesis of Clostridium ljungdahlii during the autotrophic fermentation with CO/CO2 could be observed, which occurred surprisingly in the late-log phase rather than in the transition phase. The gene expression profiles indicated that aor1, one of the putative aldehyde oxidoreductases in its genome played a critical role in the formation of ethanol, and its transcription could be induced by external acids. Moreover, a low amount of CaCO3 was proved to have positive influences on the cell density and substrate utilization, followed by an increase of over 40% ethanol and 30% acetate formation.